The quiescent centre and root apical meristem: organization and function. (25th September 2021) - Dubrovsky, Joseph G; Vissenberg, Kris
Abstract: This special issue is dedicated to the 100th anniversary of the birth of Frederick Albert Lionel Clowes, who discovered the quiescent centre (QC) of the root apical meristem (RAM). His discovery was a foundation for contemporary studies of the QC and RAM function, maintenance, and organization. RAM function is fundamental for cell production and root growth. This special issue bundles reviews on the main tendencies, hypotheses, and future directions, and identifies unknowns in the field.